Physiologic and molecular characterization of a novel murine model of metastatic head and neck cancer cachexia. Issue 5 (6th July 2021) - Olson, Brennan; Norgard, Mason A.; Levasseur, Peter R.; Zhu, Xinxia; Marks, Daniel L.
Abstract: Background: Cancer cachexia is a metabolic disorder characterized by the progressive loss of fat and lean mass that results in significant wasting, ultimately leading to reduced quality of life and increased mortality. Effective therapies for cachexia are lacking, potentially owing to the mismatch in clinically relevant models of cachexia. Specifically, cachexia observed in a clinical setting is commonly associated with advanced or late‐stage cancers that are metastatic, yet pre‐clinical metastatic models of cachexia are limited. Furthermore, the prevalence of cachexia in head and neck cancer patients is high, yet few pre‐clinical models of head and neck cancer cachexia exist. In addition to these shortcomings, cachexia is also heterogeneous among any given cancer, whereas patients with similar disease burden may experience significantly different degrees of cachexia symptoms. In order to address these issues, we characterize a metastatic model of human papilloma virus (HPV) positive head and neck squamous cell carcinoma that recapitulates the cardinal clinical and molecular features of cancer cachexia. Methods: Male and female C57BL/6 mice were implanted subcutaneously with oropharyngeal squamous cell carcinoma cells stably transformed with HPV16 E6 and E7 together with hRas and luciferase (mEERL) that metastasizes to the lungs (MLM). We then robustly characterize the physiologic, behavioural, and molecular signatures during tumour development in two MLM subclones. Results: Mice injected with MLM tumour cells rapidly developed primary tumours and eventual metastatic lesions to the lungs. MLM3, but not MLM5, engrafted mice progressively lost fat and lean mass during tumour development despite the absence of anorexia ( P  < 0.05). Behaviourally, MLM3‐implanted mice displayed decreased locomotor behaviours and impaired nest building ( P  < 0.05). Muscle catabolism programmes associated with cachexia, including E3 ubiquitin ligase and autophagy up‐regulation, along with progressive adipose wasting and accompanying browning gene signatures, were observed. Tumour progression also corresponded with hypothalamic and peripheral organ inflammation, as well as an elevation in neutrophil‐to‐lymphocyte ratio ( P  < 0.05). Finally, we characterize the fat and lean mass sparing effects of voluntary wheel running on MLM3 cachexia ( P  < 0.05). Conclusions: This syngeneic MLM3 allograft model of metastatic cancer cachexia is reliable, consistent, and readily recapitulates key clinical and molecular features and heterogeneity of cancer cachexia. Because few metastatic models of cachexia exist—even though cachexia often accompanies metastatic progression—we believe this model more accurately captures cancer cachexia observed in a clinical setting and thus is well suited for future mechanistic studies and pre‐clinical therapy development for this crippling metabolic disorder.